Analisis Kualitas Udara Ambien Parameter SO2 dan NO2 dengan Metode Passive Sampler di Kabupaten Bojonegoro - Adelia Dwi Kusuma Ningrum; Aussie Amalia (Jurnal Serambi Engineering, 2025)
Ambient air quality is a crucial factor affecting human health and the environment. This study aims to analyse the air quality in Bojonegoro Regency through monitoring using the passive sampler method. Monitoring was conducted in four areas: industrial, office, residential and traffic zones. The measured parameters included the concentrations of nitrogen dioxide (NO₂) and sulphur dioxide (SO₂), which were then calculated to determine the Air Quality Index (AQI). The analysis results showed that the average NO₂ concentration in the first phase was 6 µg/m³, rising to 9.25 µg/m³ in the second phase. Meanwhile, the average SO₂ concentration was 11.25 µg/m³ in the first phase and 11.5 µg/m³ in the second phase. The Air Quality Index showed a decrease from 85.784 to 83.160, but remained in the "Good" category. The decrease in the AQI was influenced by increased human activities and environmental conditions such as vehicle and industrial emissions. To improve the AQI to the "Very Good" category, recommended measures include public education, energy efficiency, application of clean technologies, forest protection, shift to public transport and improvement of monitoring systems.